A retrospective study on patients with breast cancer curatively treated at Hue University Hospital From 2013-2016 - Tue, Vo Minh; Cau, Nguyen Van; Vi, Le; Truong, Nguyen Chi; Dung, Ho Xuan (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.